(untitled) - AKINOLA , A. O.; OBAYELU , A. E.; SHITTU , A. M.; AKINBODE , S. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study assessed production efficiency and its determinants in cassava-based production in Ogun State. Multistage sampling procedure was used to select 174 cassava-based farmers in a cross-sectional survey. Data were analyzed using descriptive statistics, Stochastic Production Frontier (SPF) and Stochastic Cost Function (SCF) models. Results revealed that 79.3% of the cassava-based farmers were male, 89.1% were married, while 35.6% had primary education. Also, the mean age, farming experience, farm and household sizes of the farmers were 50 years, 22.9 years, 3 hectares and 6 persons respectively. The mean technical, allocative and economic efficiencies of the farmers were 0.8054, 0.8414 and 0.6835 respectively. Furthermore, farm size, quantity of fertilizer, cassava stem cutting, quantity of insecticide were the significant factors influencing cassava outputs (p<0.01) while household size, educational status, credit use and extension contact decreased the technical inefficiency of the farmers (p<0.01). Stochastic cost function showed that prices of cassava stem cutting, price of fertilizer, price of herbicide and price of insecticide were the significant determinants of the total cost of production (p<0.05) while credit use, extension contact, sex and educational status increased cost efficiency (p<0.05). The study concluded that the farmers were not fully efficient in their resource allocation; therefore, there is allowance for improvement through intensive collaboration with extension services and required institutions. The study therefore advocated for adequate credit facilities and extension services to be made available to cassava-based farmers in the study area in order to increase their production efficiency.